2013
DOI: 10.1177/0333102413479834
|View full text |Cite
|
Sign up to set email alerts
|

The typical duration of migraine aura: A systematic review

Abstract: The data indicate the duration of NHMA may be longer than one hour in a significant proportion of migraineurs. This seems to be especially true for non-visual aura symptoms. The term probable seems inappropriate in ICHD-III so we propose reinstating the category of prolonged aura for patients with symptoms longer than an hour and less than one week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 24 publications
4
46
0
2
Order By: Relevance
“…However, in severe attacks, even non-motor symptoms occasionally last more than a few days or even weeks 2 3. Spreading depression (SD), which is a short-lasting slowly propagating wave of neuronal and glial depolarisation, is widely accepted as mechanism underlying visual aura,4 5 but the mechanism underlying prolonged aura symptoms remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…However, in severe attacks, even non-motor symptoms occasionally last more than a few days or even weeks 2 3. Spreading depression (SD), which is a short-lasting slowly propagating wave of neuronal and glial depolarisation, is widely accepted as mechanism underlying visual aura,4 5 but the mechanism underlying prolonged aura symptoms remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The aura symptom spreads gradually over a period of 5 minutes and (for each individual aura) lasts between 5 and 60 minutes (although this upper limit was set arbitrarily). Indeed, it has been reported that aura lasts for more than one hour in up to 37% of patients [14]. This epidemiological reality has been recently taken into consideration in the third edition of the International Classification of Headache Disorders, in which aura lasting more than an hour but less than a week (in the absence of radiologically confirmed brain ischemia) was defined as “probable migraine with aura (prolonged aura)” [15].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review of the usual duration of migraine aura found that migraine aura lasted longer than 1 h in a significant proportion of migraineurs (up to 60% in aphasic aura) 4. The authors' suggested labelling of these patients as having probable, rather than definite, migraine is inappropriate.…”
Section: What Is Migraine? the Headache Premonitory Symptoms The Aumentioning
confidence: 99%